College Algebra - Zill, Dennis G. (McGraw-Hill Publishing Company, 1990)
Fundamental Concepts of Algebra, Equations and Inequalities. Functions and Graphs. Polynomial and Rational Functions. Exponential and Logarithmic Functions. Topics in Analytic Geometry. Systems of Equations and Inequalities. Matrices. Squences...